Zarco - An autonomous craft for underwater surveys - Nuno Cruz (2007)
The autonomous surface craft (ASC) Zarco is a small size craft developed at Porto University and designed to perform autonomous missions mainly in river dams and estuarine environments, either serving as a moving navigation beacon for underwater vehicles or collecting high resolution interferometric synthetic aperture sonar (In-SAS) data. This paper describes the main systems of Zarco and presents preliminary results concerning the performance of the on-board control system, obtained in test missions. Another paper presented in this conference addresses the In-SAS system